The influence of ethics, experience, and competence on auditors’ professional skepticism (Study at BPKP representative of Lampung Province) - Panca Tirta Yasa; Yuliansyah Yuliansyah; Ninuk Dewi Kesumaningrum (Jurnal Studi Pemerintahan dan Akuntabilitas, 2021)
Purpose: This study aims to prove empirically the influence of ethics, experience, and competence on auditors’ professional skepticism. Research Methodology: In testing the hypotheses, 63 auditors at BPKP Representative of Lampung Province took part in responding to the questionnaires distributed. The criteria for auditors sampled: 1). Auditors who are directly involved in the assignment, especially in the process of collecting and testing audit evidence, like audit team members, audit team leaders, audit supervisors and audit quality control, and 2). Auditors who are experienced in auditing for at least one year. Partial Least Square analysis method was used and processed with SmartPLS version 3.0 software and Microsoft office excel 2007 program. Results: As hypothesized, the results revealed that ethics, experience, and competence had a positive influence on auditor professional skepticism. Discussion, limitations, and recommendations for future research are discussed. Limitations: This research is limited only to the government auditors working at BPKP Representative of Lampung Province so that the research result can not be generalized to the auditor as a whole. The auditor's tight schedule caused the returning time of questionnaires to shift from the set timeline previously. The use of questionnaires also was the last limation in terms of inaccurate answers, dishonest answers, and missinterpreted questions. Contribution: This study is beneficial for BPKP Representative of Lampung in improving auditors' professional skepticism, as well as one of literature resources for conducting further studies. Keywords: Ethics, Experience, Competence, Auditors’ professional skepticism, Auditor